2014
DOI: 10.1055/s-0034-1370780
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recurrent Tracheoesophageal Fistulas: A Systematic Review

Abstract: OS for RTEF has a low morbidity and mortality, a higher success rate, and requires fewer treatments than an endoscopic repair. The ideal ET is undecided but it remains a viable alternative provided treatment failures are anticipated and prompt redo treatments initiated to prevent ongoing respiratory morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…In a systematic review of 165 patients across 44 studies [5], the success rate of surgery was found to be 93.5% compared with 84% for endoscopic treatment. In our study, patients had either failed endoscopic management prior to their referral to our institution or they were too large to be suitable for this approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review of 165 patients across 44 studies [5], the success rate of surgery was found to be 93.5% compared with 84% for endoscopic treatment. In our study, patients had either failed endoscopic management prior to their referral to our institution or they were too large to be suitable for this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas endoscopic management alone of these has been described [ 7 ], our preference has been to perform surgical repair because of the high risk of recurrence after conservative management. In a systematic review of 165 patients across 44 studies [ 5 ], the success rate of surgery was found to be 93.5% compared with 84% for endoscopic treatment. In our study, patients had either failed endoscopic management prior to their referral to our institution or they were too large to be suitable for this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reoperation against recurrent TEF is usually done with the interposition of the surrounding soft tissues such as the pleura, pericardium, and muscle flaps [ 2 , 7 ]. However, up to 21% of cases, experience refistulization with mortality rates reaching approximately 4% [ 2 , 4 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…TEF can be managed either surgically (open repair or thoracoscopic) or endoscopically, depending on their etiology, size, anatomy, and patient comorbidities [4]. Surgery is highly invasive and other options are typically investigated before this is undertaken.…”
Section: Introductionmentioning
confidence: 99%